USING CONTEMPORARY TECHNOLOGIES TO TEACH VOCABULARY (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
In addition to discussing contemporary methods that can be useful in foreign language instruction, the paper addresses the problems associated with analyzing the peculiarities of teaching vocabulary and learning strategies based on its integrated use.